Effect of Different Doses of Goat Manure on Growth and Production of Curly Chili (Capcisum annum L.): Pengaruh Aplikasi Dosis Pupuk Kotoran Kambing Berbeda Terhadap Pertumbuhan dan Produksi Tanaman Cabai Keriting. - Ni Komang Sri Suartini; Anggia Anggia (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
Studies on the use of goat manure have been carried out, but no one has yet examined in detail about the use of the correct dosage of goat manure on specific soils in Southeast Sulawesi, especially in the city of Baubau. The purpose of this study was to determine the effect of different goat manure doses on the growth and production of curly chili plants. This research was conducted from July to September 2018 which took place in the Ngkari-Ngkari sub-district, Bungi sub-district, Baubau city, Southeast Sulawesi Province. This study used a randomized block design (RBD) consisting of one factor, namely variations in the use of goat manure with 7 levels of treatment; P0 (0 ton h1 goat manure), P1 (3 tonnes h1 goat manure), P2 (6 tonnes h1goat manure), P3 (9 tonnes h1 goat manure), P4 (12 tonnes h1goat manure), P5 (15 tonnes h1goat manure) and P6 (18 tonnes h1goat manure). The analysis design used is the analysis of variance (ANOVA). The variables observed in this study included plant height, number of stems, stem diameter, number of fruits and plant production. Based on the results of the study that different doses of goat manure treatment can significantly affect plant height, number of stems, number of fruits and fruit production on curly chili plants. P6 treatment with a dose of 18 tons of fertilizer h1goat manure is the best dose of fertilizer to increase growth and fruit production of curly chili plants. Keywords: Dosage of goat manure, growth and production